The 'White' Mask and the 'Gypsy' Mask in Film - Mladenova, Radmila (Antiziganismusforschung interdisziplinär - Schriftenreihe der Forschungsstelle Antiziganismus, 2022)
The study ventures into a topic that has been so far largely neglected in film studies: the 'gypsy' phantasm on the big screen. It reconstructs the history of 'gypsy' representations in film since the birth of the medium providing a systematic film-theoretical analysis of their aesthetic and social functions. Based on a corpus of over 150 works from European and US cinema, it is shown that 'gypsy'-themed feature films share the pattern of an 'ethno-racial' masquerade, irrespective of the place and time of their origin. The author thus expands the research, concentrated until now in the field of literature, with another art form, film, opening up new dimensions of (popular) cultural antigypsyism.